Impact of sodium chloride on wheat doughs - Mak, Sze Pui Cheryl (2009)
The impact of salt (sodium chloride) on the wheat dough was studied, with a particular focus on the state and distribution of water and sodium in the dough system. In this study, dough samples were prepared using the same processing techniques as in commercial bakery (i.e. Chorleywood Bread Process) and were investigated simultaneously using molecular spectroscopy 1[subscript]H and 23[subscript]Na NMR), deformation stress measurement (Kieffer test, Texture Profile Analysis and Chen-Hoseney test) and calorimetry (DSC). A progressive study of experimentation was carried out in which dough samples between zero and 5% added salt (on flour base) to exaggerate the effects of salt. Furthermore, test baking was also used to study the mechinability of doughs. All of the techniques studied enabled the construction of a complete picture of the sequential events occurring when salt is reduced.